Estudar o turismo hoje: para uma revisão crítica dos estudos de turismo - Sampaio, S. (2013)
Aproveitando a publicação, em 2009, de The Sage Handbook of Tourism Studies e de The Sociology of Tourism: European Origins and Developments – duas extensas antologias sobre o estudo do turismo nas ciências sociais –, o artigo discute as tradições aca- démicas que cada um destes volumes representa e defende, nomeadamente, uma tradição anglófona transatlântica e uma tradição europeia continental. Identificam- -se algumas tendências dominantes para, no final, se propor a “rematerialização” dos estudos de turismo partindo de um ponto de vista local, focado nas práticas e sensível às assimetrias visíveis (ou não) no terreno. The article takes the publication, in 2009, of The Sage Handbook of Tourism Studies and The Sociology of Tourism: European Origins and Developments – two anthologies that review how tourism has been studied in the social sciences – as an opportunity to discuss the traditions represented and defended in each of these books, namely: a transatlantic Anglophone tradition, and a European continental one. Some of the main tendencies are identified, so as to propose, in the end, the “rematerialization” of tourism studies through the adoption of a local point of view that focuses on the practices, but is also sensitive to the asymmetries that are visible (or not) from the ground.